Clinical characteristics and diagnosis of the COVID-19 in patients in COVID outpatient clinics - Petrov Kiurski, Miloranka; Živanović, slavoljub (General Practice, 2022)
Objective. Examine clinical manifestations, PCR test results, and visit outcomes in patients in COVID-outpatient clinics. Method. The survey was performed using the questionnaire, in February 2021. in patients in four COVID-outpatient clinics in Belgrade and one in Subotica. We got the data about their jobs, gender, age, present symptoms and comorbidities, PCR-testing, and visit outcomes. The data were processed using the software statistical package SPSS 17. Statistical significance was defined for level p<0,05. Results. We included 676 participants, of both genders, with an average age of 49. They visited the doctor 1-3 days after symptoms onset. The most common symptoms were fever and cough, followed by fatigue and muscle aches. Hypertension and obesity were the most common comorbidities, mostly in patients over 65 (p=0,000). We tested 92% of the participants, using PCR tests, and out of 676, 60,95% tested PCR positive, mostly those over 50 (p=0,010). Due to the disease severity, 17,3% of the participants were referred to the hospitals, mostly those aged 51 to 65, but the difference wasn`t statistically significant (p=0,183). Conclusion. The most common symptoms of the COVID- 19 were high temperature and cough, and the participants visited the doctor 1 to 3 days after symptoms onset. Hypertension and obesity were the most common comorbidities, more often in participants over 65. The PCR tests were positive in more than half of the participants, mostly in those over 50.